Making Sense of Immigrant Work Integration An Organizing Framework - Nardon, Luciara; Hari, Amrita; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This open access book explores the wicked problem of immigrant work integration, with specific examples from Canada. Bringing together a variety of disciplinary perspectives, it discusses immigrant work integration as a process of sensemaking, involving multiple actors (immigrants, organizations, communities, and governments) and multiple scales (individual, interactional, organizational, and institutional). The authors identify key players, issues, practices of support, and avenues for future research. This work contributes to enhancing the social impact of academic research by providing a comprehensive overview of the field of immigrant work integration for researchers in global mobility and organizational studies, as well as practitioners. Luciara Nardon is Professor of International Business at the Sprott School of Business at Carleton University, Canada. Her research explores cultural and cognitive influences on work in multicultural environments. She has published books and academic articles on topics related to migration and cross-cultural management. Amrita Hari is Associate Professor in the Feminist Institute of Social Transformation at Carleton University, Canada. Her research interests lie within global migrations, transnationalism, diaspora, and citizenship. She has published her research in various academic journals on migration and gender.
Chapter 1: Immigrant Work Integration: A Wicked Problem -- Chapter 2: The Sensemaking Perspective -- Chapter 3: The Immigrant Sensemaker -- Chapter 4: Powerful Interactions for Integration -- Chapter 5: Organizing for Immigrant Workforce Integration -- Chapter 6: The Macro Context of Immigration -- Chapter 7: Extending Sensemaking of Immigrant Integration.
Keywords: International business enterprises; Personnel management; Management; Industrial organization; International Business; Human Resource Management; Management; Organization